Penerapan Media Pembelajaran Berbasis ICT FUNKTECH (Fungsi Kuadrat with Technology) Untuk Meningkatkan Pemahaman Konsep Matematika Pada Siswa Kelas X - Azzahro, Fatima (Maliki Interdisciplinary Journal, 2025)
The purpose of this classroom action research was to improve Grade X students’ understanding of mathematical concepts, specifically on the topic of quadratic functions, through the use of an ICT-based learning media called FUNKTECH (Fungsi Kuadrat With Technology). This research was motivated by students' lack of understanding of the quadratic function concept, which was reflected in unsatisfactory learning outcomes and low student participation during conventional learning processes. The research was carried out in two cycles, each consisting of the stages of planning, action implementation, observation, and reflection. The subjects of this study were 23 Grade X students at MAN 1 Kota Probolinggo. Data were collected through concept understanding tests, student activity observations, and student response questionnaires regarding the learning media. The results showed that students’ conceptual understanding improved from a pre-action average score of 47 (with a mastery rate of 39.13%) to 74 in Cycle I (mastery rate of 65.22%), and further increased to 82 in Cycle II (mastery rate of 86.96%). In addition, the FUNKTECH learning media effectively enhanced student participation and created a more interactive and enjoyable learning environment. As many as 91.7% of students gave positive responses and agreed with the use of the FUNKTECH media. Therefore, ICT-based learning media is effective in improving students’ understanding of mathematical concepts, particularly in the topic of quadratic functions.